Quand l’économie écologique dé-nature la justice environnementale - Laurie Gagnon-Bouchard (VertigO)
Despite the abundance of environmental justice literature, there are few articles examining the conceptualization of nature within it. Yet critical theorists of decolonial thought, ecofeminism and poststructuralism have shown that the representation of nature is not innocent and often participates in reinforcing power relations already at work. In this article, I propose to question the conceptualization of nature as a place of power relation and as a historically and socially constructed notion. As a first step, this article presents an historical reminder of the emergence of the notion of environmental justice alongside the civil rights movement in the United States. Next, I propose to examine the conceptualization of nature within the two major approaches of the environmental justice literature (ecological economics and socioecology) to see if they participate in the imposition of a Western-centered definition. With regard to the theoretical framework, the results of the analysis show that the theoreticians (Hornborg and Martinez-Alier) of the ecological economics approach, which requires a standardization of the language of the struggles, mobilize a western-centered and modern conception of nature and by doing so, fails to escape the colonial logic they criticize.